ANALYSING THE SELF- IMAGE OF WOMAN USERS TOWARD KOREAN SKIN CARE PRODUCT IN MANADO - Sundah, Gabriela Queenlibraini; Lapian, Joyce S.L.H.V.; Pandowo, Merinda H.C (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract:  Self Image is how people feel about themselves as a people, as human beings, it is  who you are as a person from the soul  and the most important sometimes people measure and make perception about the self image based on what they use or wear.  Self image also is about how people feel about the appaerance and every people have their own way to measure the self image.The aim of this study is to analyze the self -image and also to analyze how is the self image of woman user when using korean skin care product in Manado. In order to achieve these objectives the researcher got information from 10 respondents using qualitative study which is in-depth interview and uses purposive and snowball sampling. The results showed that self image on woman users or woman consumer has been increasing and refers to the positive side when woman consumer using the korean skin care product and the results is as the expectation which the product itself suit toward them, all the respondent gives a positive opinion towards the self image when using the korean skin care product or known as foreign products and the korean skin care product is a product that valuable among the consumer that have an experience of using the product itself cause the product mostly use natural ingredients. The recommendation, For the consumer, it is  good  for the consumer to know about the self image toward them and what factors that leads them to use korean skin care and whats increase the self image. Keywords: self image, woman user, korean product